2022
DOI: 10.3390/molecules27144422
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition, Bioactive Components, and Hepatoprotective Activity of Fruit Vinegar Produced from Ningxia Wolfberry

Abstract: Wolfberry (Lycium barbarum L.) is a nutritious and medicinal fruit, and deeply processed products of wolfberry needs to be improved. In this study, nutrition, bioactive compounds, and hepaprotective activity were explored in wolfberry vinegar (WFV). The contents of nutrients including total sugar and protein in WFV samples were 2.46 and 0.27 g/100 mL, respectively. Total phenolic and flavonoid contents in WFV were 2.42 mg GAE/mL and 1.67 mg RE/mL, respectively. p-Hydroxybenzoic acid and m-hydroxycinnamic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…Furthermore, there is a protective effect of wolfberry fruit vinegar on the liver. It was found that wolfberry fruit vinegar treatment effectively alleviated liver injury by inhibiting oxidation levels and increasing antioxidant levels in CCl 4 -treated mice [95]. Taken together, the fermentation process of wolfberry fruit vinegar can improve the utilization rate of raw materials, screen excellent strains, and enhance fermentation efficiency, which are the key factors to control cost.…”
Section: Wolfberry Fruit Vinegarmentioning
confidence: 96%
“…Furthermore, there is a protective effect of wolfberry fruit vinegar on the liver. It was found that wolfberry fruit vinegar treatment effectively alleviated liver injury by inhibiting oxidation levels and increasing antioxidant levels in CCl 4 -treated mice [95]. Taken together, the fermentation process of wolfberry fruit vinegar can improve the utilization rate of raw materials, screen excellent strains, and enhance fermentation efficiency, which are the key factors to control cost.…”
Section: Wolfberry Fruit Vinegarmentioning
confidence: 96%
“…Wolfberry, rich in polyphenols, antioxidants, total sugar, and protein, demonstrates significant efficacy in alleviating liver injury induced by toxicants like CCl4 in mice. It achieves this by improving histopathological changes, reducing liver biochemical indices, and enhancing antioxidant capacity, thus offering protection against oxidative liver injury [26,27] .…”
Section: Hepatoprotective Effectmentioning
confidence: 99%
“…LBP was assayed by phenol-sulfuric acid method reference to GB/T 18672-2014 Appendix A of CNS (Yu et al, 2017). CP was assayed by Kjeldahl method reference to GB 5009.5-2016 of CNS (Tian et al, 2022). Mn was assayed by flame atomic absorption spectrophotometry (FAAS) at 279.5 nm reference to GB 5009.242-2017 of CNS (Wang et al, 2021).…”
Section: Hyperspectral Measurement and Chemical Analysismentioning
confidence: 99%